Pelatihan Pembuatan Media Pembelajaran Matematika Berbasis Arduino - Nanndo Yannuansa; Humaidilah Kurniadi K.W2; Nailul Izzati; Imamatul Ummah; Jati Widyo Leksono; Elly Indawati (Jurnal Pengabdian Masyarakat Universitas Darul Ulum, 2024)
Engaging and interactive learning media play a crucial role in enhancing students' interest and understanding of subjects, including Mathematics. One of the technologies that can be utilized is Arduino, an open-source electronics platform that enables the development of innovative learning media. This study aims to conduct training on the creation of Arduino-based Mathematics learning media for teachers as an effort to enhance their pedagogical and technological competencies. The training methods include theoretical material delivery, hands-on practice, and collaborative discussions. Evaluation results indicate that the training successfully improved teachers' abilities to design and implement Arduino-based learning media. The success of the community service program was demonstrated by 90% of participants being able to design and create prototypes of Arduino-based learning media. The resulting media effectively help students understand Mathematical concepts such as geometry, measurement, and number patterns. Therefore, this training serves as a strategic step in integrating technology with more innovative and relevant Mathematics teaching